Mendesain Kurikulum Merdeka Berbasis Kearifan Lokal: Studi Kajian Pustaka - Nia Farhanis; Sahroni; Rokimin (Yayasan Dinamika Ilmu Banyuwangi, 2025)
The implementation of the Independent Curriculum in Indonesia is projected to be a strategic effort to create relevant, flexible, and contextually relevant learning. However, in practice, the integration of local wisdom is still often treated peripherally and has not been systematically designed. This study departs from the Indonesian national context by positioning the Independent Curriculum as an educational policy framework that directly confronts socio-cultural diversity and the risk of curriculum homogenization. This study aims to explore the conceptual pattern of local wisdom integration in the Independent Curriculum and formulate a curriculum design framework that is argumentative and applicable. The method used is a qualitative literature review, with a systematic review design, of journal articles, academic books, and relevant policy documents published in the last ten years, analyzed through a thematic-critical approach. The results of the study indicate that the literature forms a relatively consistent conceptual pattern, structured around dimensions of integration, principles of integration, and operational indicators, and positions local wisdom as a learning context bridged through content integration, contextual pedagogy, and authentic assessment. The key novelty of this study lies in modeling the integration of local wisdom as a layered curriculum design that links learning outcomes to the supporting institutional ecosystem, including teacher capacity, school support, and adaptive curriculum governance. These findings imply the need for a policy shift from mere content flexibility to strengthening curriculum design and the implementation ecosystem to ensure consistent, meaningful, and sustainable integration of local wisdom.